Estratégias, condições e obstáculos para implantação de técnicas mais sustentáveis no manejo da água em assentamentos rurais. Caso: assentamento rural Horto Vergel 12 de outubro , Mogi Mirim-SP - Barboza, Renato Matos de Lopes Torres (Universidade Federal de São Carlos, 2011)
When we analyze the basic needs of human beings, the quantity and quality of available water determines the life quality of a family or community. This research brings to light the importance of access to water to ensure the basic needs of rural communities based on social inclusion and self-sufficiency. A unique case study, based on Martin (2008), was proposed to study water management in the Rural Settlement Horto Vergel in Mogi Mirim-SP. The proposal aims to bring up the strategies and analyze the conditions and obstacles to implement more sustainable techniques in water management in rural settlements. A diagnosis of the settlement was developed based on a survey of existing documents, interviews with settlers, leaders, agents and Technical Assistance and Rural Extension (Ater) institutions working on site, as well as practical activities for implementation and evaluation of participatory methodologies developed during the research. It was found that sustainability in management and conservation of water in the settlement is directly linked to its historical development (camping, entering the lot, opening the water hole wells, installation of the power grid, semi artesian wells, opening of wells, installation of network distribution system, and creation of the rural district), forms of public investment and organizational models used. The institutions of Ater should systematize the adapted technologies for family agriculture already charted and/or tested related to water management and conservation, and develop instruments that will ensure the continuity and transfer of information between entities and teams. The existence of structural and organizational problems within the settlement, in addition to insufficient financial resources, lack of alternative methods and technologies, and research on water management and conservation by the Ater specialists, have interfered and still complicate the development process of the settlement.
Keywords: Agroecologia; Assentamentos rurais; Água - manejo; Permacultura; Tecnologia social; Manejo e conservação da água; Metodologias Participativas.; Rural settlement; Water management and conservation; Agroecology; Permaculture; Social technology; Participative Methodologies; ENGENHARIAS